THE EFFECT OF ISLAMIC MARKETING MIX AND BRAND IMAGE ON PURCHASING DECISIONS AT CANTING BATIK STORES IN BANDA ACEH - Mauliani, Mela; Nizam, Ahmad (Universitas Syiah Kuala, 2024)
The study aims to determine the effect of Islamic marketing mix and brand image on purchasing decisions at batik canting shops in Banda Aceh. This research uses quantitative methods, where the population used in this study are canting batik customers with a sample of 82 respondents obtained through purposive sampling technique. The data used in this study are primary data. Primary data was obtained from distributing questionnaires to respondents. The analysis used is Multiple Linear Regression. The results of this study indicate that partially the product and brand image variables have no effect on purchasing decisions, while the price, place, and promotion variables partially have a positive and significant effect on purchasing decisions. Then simultaneously, the variables of product, price, place, promotion and brand image have a positive and significant effect on purchasing decisions at the Canting Batik shop in Banda Aceh. Therefore, it is hoped that the cantng batik shop can pay more attention to brand image and improve products both in terms of quality and quantity.Keyword : Islamic Marketing Mix,Brand Image, purchasing decisions